Teledermatology Adaptations in the COVID-19 Era - Edwards, Harrison A.; Shen, Xiaohua; Soyer, H. Peter (Frontiers in Medicine, 2021)
The COVID-19 pandemic has required health services worldwide to adapt to dramatically changing healthcare needs and risks across all medical specialties. In the dermatology department at Princess Alexandra Hospital, Brisbane, Australia, we developed and implemented a teledermatology system with 1 week's notice to help reduce infection risk bidirectionally, while saving patients many hours of travel and waiting time with acceptable technological substitutes for the clinical encounters. In this study, we report the efficacy and tolerability of our telephone consultation and store and forward imaging system, including patient experience from validated survey data. Our design, implementation and usage of a remote-default system provides experience and lessons to draw upon in developing future telemedicine systems to address dermatology service maldistribution – an issue affecting large areas of Australia – as well as preparedness for future infection mitigation requirements.